A real-world study in patients with type 2 diabetes mellitus treated with gliclazide modified-release during fasting: DIA-RAMADAN. (May 2020) - Hassanein, Mohamed; Al Sifri, Saud; Shaikh, Shehla; Abbas Raza, Syed; Akram, Javed; Pranoto, Agung; Rudijanto, Achmad; Shaltout, Inass; Fariduddin, Md; Mohd Izani Wan Mohamed, Wan; Al Awadi, Fatheya; Alessa, Thamer; et al.
Abstract: Aims: To explore the real-world safety and effectiveness of gliclazide modified release (MR) in patients with type 2 diabetes mellitus (T2DM) fasting during Ramadan. Methods: DIA-RAMADAN (NCT04132934) was a prospective, international, observational study conducted in nine countries. Patients >18 years of age with T2DM (N = 1244) were examined at an inclusion visit (V0) occurring 6–8 weeks before the start of Ramadan. Patients received a diary to report treatment changes, hypoglycaemic events (HEs), and other adverse events. Gliclazide MR was taken once daily for 14–18 weeks. A second visit (V1) was conducted 4–6 weeks after the end of Ramadan. The primary endpoint was the proportion of patients reporting ≥1 symptomatic HE. Changes in HbA1c, fasting plasma glucose (FPG), and body weight were secondary endpoints. Results: The proportion of patients reporting ≥1 symptomatic HE during Ramadan was low (2.2%) with no reported severe HEs. There was a significant reduction in HbA1c (−0.3%), FPG (–9.7 mg/dL), body weight (−0.5 kg) and body mass index (−0.2 kg/m 2 ) between V0 and V1 (p < 0.001). Conclusions: Patients with T2DM treated with gliclazide MR during Ramadan have a low risk of hypoglycaemia and maintain glycaemic control and weight while fasting.